Research on Dwell Time of SS316L in Wire Arc Additive Manufacturing Using Simulation - BIN DIN, IDHAM NUR HAKIM; Mohd Halim Irwan Ibrahim; Sarah Nadiah Mohd Ghazali (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Wire Arc Additive Manufacturing (WAAM) offers an efficient and sustainable method for producing large metal components with reduced material waste. Among the materials commonly used, SS316L stainless steel is widely favored for its excellent corrosion resistance and mechanical properties, making it ideal for applications in aerospace, marine, and medical industries. However, controlling the heat generated during the layer-by-layer process remains a major challenge. One of the most influential parameters is dwell time, which refers to the pause between each deposited layer. This study explores the effect of dwell time on the thermal behaviour, deformation, and residual stress of SS316L components using numerical simulation. Simufact Welding software was used to simulate different dwell time settings across three-layer configurations. The Taguchi method was applied to design the experiments and identify optimal parameters with minimal trials. The results show that shorter dwell times, especially at lower layer counts, significantly improve dimensional accuracy and reduce residual stress. The combination of 15 seconds dwell time with 5 layers produced the most stable results. These findings highlight the importance of dwell time in controlling thermal accumulation and improving build quality. This research contributes practical insights for process optimization in WAAM and supports its broader industrial application.